Relatório de estágio técnico profissional em medicina veterinária: nutrição e reprodução de ruminantes - Ceratto, Christian Anghinoni (2023)
The Supervised Professional Technical Internship (ETPS) was carried out in the area of ​​Ruminant Nutrition and Reproduction, under the academic guidance of Prof. Dr. Laura Beatriz Rodrigues and under the local supervision of Veterinary Doctor Rubimar Franco, from July 12th to August 25th and with Veterinary Doctor Carlos Humberto Barth from August 28th to November 10th, totaling 528 hours. During the period, diet formulations, nutritional and reproductive management of lactating cattle were monitored. This report describes the internship location and all monitored activities divided into areas of activity. Afterwards, reproduction protocols will be reported according to the lactation days of dairy cows. ETPS was an extremely important phase for my development, both professional and personal. During it, I was able to learn about the routine in the field, in addition to interacting with producers and other professionals in this field, always adding more knowledge. The opportunity to witness different realities, different experiences, made my knowledge grow, not only about Veterinary Medicine, but also other aspects, which include agricultural activity.